Kebutuhan gizi untuk anak usia dini - Ningsih, Rizka Septia (Maliki Interdisciplinary Journal, 2025)
A person's growth and development in children is influenced by their daily food consumption, thus affecting the nutritional status of children. The nutritional status of children will be good if their bodies receive sufficient nutrition so that they efficiently enable physical growth, brain development, work ability and better health in children. Therefore, to maintain the nutritional needs of children so that they are met, it is necessary to make several efforts to fulfill nutritional requirements for children at an early age. If parents are negligent in meeting the nutritional needs of children at an early age, it can have the impact of hampering the child's growth and development and this impact can be long-term which can put the child at risk in the future. Therefore, this article will discuss how parents can meet the nutritional needs of early childhood, choosing food ingredients, and solutions for preparing nutritious food for children.